Iris domestica (iso)flavone 7- and 3′-O-Glycosyltransferases Can Be Induced by CuCl2 - Zhang, Xiang; Zhu, Yan; Ye, Jun; Ye, Ziyu; Zhu, Ruirui; Xie, Guoyong; Zhao, Yucheng; Qin, Minjian (Frontiers in Plant Science, 2021)
In many plants, isoflavones are the main secondary metabolites that have various pharmacological activities, but the low water solubility of aglycones limits their usages. The O-glycosylation of (iso)flavones is a promising way to overcome this barrier. O-glycosyltransferases (UGTs) are key enzymes in the biosynthesis of (iso)flavonoid O-glycosides in plants. However, limited investigations on isoflavonoid O-UGTs have been reported, and they mainly focused on legumes. Belamcanda chinensis (L.) DC is a non-legume plant rich in various isoflavonoid glycosides. However, there are no reports regarding its glycosylation mechanism, despite the previous B. chinensis transcriptome being annotated as having non-active isoflavone 7-O-UGTs. Our previous experiments indicated that isoflavonoid glycosides were induced by CuCl2 in B. chinensis calli; therefore, we hypothesized that isoflavone O-UGTs may be induced by Cu2+. Thus, a comparative transcriptome analysis was performed using B. chinensis seedlings treated with CuCl2, and eight new active BcUGTs were obtained. Biochemical analyses showed that most of the active BcUGTs had broad substrate spectra; however, substrates lacking 5-OH were rarely catalyzed. Real-time quantitative PCR results further indicated that the transcriptional levels of BcUGTs were remarkably induced by Cu2+. Our study increases the understanding of traditional UGTs and isoflavone biosynthesis in non-legume plants.